KOHESI DAN KOHERENSI WACANA STAND UP COMEDY PRANCIS DAN INDONESIA - Anjani, Esa Agita (Jurnal Kawistara, 2013)
Stand up comedy is an art comedy show which develops rapidly in all over world nowadays. Standup comedy considered as a smart comedy. This research will concern about french and indonesianstand up comedy discourse by Tomer Sisley (french) and Raditya Dika (indonesian). This paper focuson cohesion and coherence analysis. The results showed that cohesion and coherence are the mostimportant aspect for making a good stand up comedy discourse. Cohesion aspect in stand up comedyare gramatical cohesion (reference, substitution, ellipsis, conjunction) and lexical cohesion (repetion,synonim, antonym, collocation). Also, coherence aspects are additional relation, temporal relation,oppositional relation, affectional relation, causal relation, conditional relation. Repetion is a cohesivetools which more dominate in this stand up comedy discourse.